Motivation and implementation of Islamic concept in madrasah ibtidaiyah school: Urban and rural - Alfauzan Amin; Asiyah Asiyah; Zulkarnain Syafal; Alimni Alimni; Nurlaili Nurlaili; Ayu Wulandari; Dwi Agus Kurniawan (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to see how students' motivation and understanding of the concept of Islamic religion in students in rural and urban areas. This research uses mixed-method research. Qualitative data will be supporting data for quantitative data. The sample of this study consisted of 87 students and eight teachers in urban and 99 students and eight teacher rural Islamic elementary school students with random sampling technique. Instrument in the study used a questionnaire for motivation with a Likert scale of 4 and a test for understanding the concept of Islam. In this study, there are two types of data analysis used, namely quantitative analysis using descriptive statistics (mean, standard deviation, and category), and inferential statistics (independent sample t-test) using the SPSS 21 application, for qualitative using reducing analysis, analyzing, and interpreting findings from Miles and Huberman. The findings of this study illustrated that motivation was good (M=2.88, SD=0.78) and understanding of student concepts (M=81, SD=0.77) was good too, but in rural areas are better than in urban areas. This finding has implications that the challenges of Islamic religion in urban areas are greater for students. The novelty in this study is the implicit finding of this study that external factors (school social environment, community social environment, family environment) have a major influence on motivation and understanding of Islamic religious concepts.